Psikoedukasi untuk Meningkatkan Pengetahuan Guru yang Memiliki Siswa dengan Gangguan Atensi Belajar - Ruziqna Ruziqna; Nurva Dillatul Vatin; Nurkhalisha Ersyafiani (Faculty of Ushuluddin and Humanities, 2022)
Childhood is very vulnerable to experiencing attention disorders in learning. This of course has an impact on the learning process of children. Teachers as educators cannot fully overcome these conditions due to lack of knowledge and information on how to deal with children who have attention disorders while studying. Teachers play an important role for the academic environment of children, especially children who have attention problems, both when the child has not been diagnosed and after being diagnosed with an attention disorder. This study uses an experimental research design of single subject AB. The subject in this study was a tutor who had students with learning attention problems. The analysis in this study uses thematic analysis. The results showed that the provision of psychoeducation was very useful for increasing knowledge related to learning attention in children, and the knowledge possessed by the subject was more structured so that it was easier to practice the knowledge gained while studying in class. This study concludes that teacher knowledge about the development of children's attention is very important because it supports the success of learning in the classroom.